La Impugnación de la Competencia en Asuntos Contenciosos ante la Corte Internacional de Justicia (2008)
In this comment the different procedures available to a State which is unwilling to appear before the International Court of Justice are discussed. Challenges to the Court’s jurisdiction or the admissibility of the application are explained, including the nexus of questions of jurisdiction with proceedings on provisional measures and the manner the Court handles such challenges. The analysis is based on the provisions of the Court’s Statute and Rules, as well as its abundant jurisprudence on procedural matters.